Magnetic Particle Imaging Opportunities and Challenges on the Way to the Clinic - Graeser, Matthias (XXVIII. Symposium Electromagnetic Phenomena in Nonlinear Circuits (EPNC 2024): Conference Proceedings, 2025)
Magnetic Particle Imaging is a rising medical imaging technique which visualizes the distribution of magnetic particles within the human body. Besides direct visualization of blood flow dynamics, the technique can exploit the particle magnetization dependence on micro-environmental physical parameters as microsensors to measure temperature, viscosity, or binding state. Furthermore, the particles can also act as heat generators when exposed to suitable high frequency fields enabling magnetic fluid hyperthermia and triggered drug delivery. This work reviews the opportunities offered by MPI and highlights the challenges on the way to becoming an established clinical imaging modality.